Daya Antibakteri Ekstrak Kulit Apel Manalagi (Malus sylvestris Mill.) Terhadap Pertumbuhan Streptococcus mutans (Antibacterial Activity of Manalagi Apple Peel (Malus sylvestris Mill.) Extract on The Growth of Streptococcus mutans) - Jannata Hafidata Rabbani; Gunadi Achmad; Ermawati Tantin (Pustaka Kesehatan, 2014)
Apple is a popular fruit which is consumed by many people in Indonesia. Manalagi apple's peel contains polyphenols that have antibacterial effects. Streptococcus mutans is the normal flora that can cause oral disease. One of alternative medications to prevent the disease by using natural products as antibacterial. This research is aimed to determine the antibacterial activity manalagi apple's peel extract on the growth of S. mutans and minimum concentration to inhibit growth. The method of this research is well diffusion method with 8 samples for each treatment. Samples consisted of five treatment groups which is manalagi apple's peel extract with concentration of 100%, 50%, 25%, positive control group (chlorhexidine 0.2%), and negative control group (aquadest sterile). Data were analyzed using the Kruskal-Wallis and Mann-Whitney test. The results of this research showed that manalagi apple's peel extract at all concentrations have antibacterial activity against the growth of S.mutans. Minimum inhibition concentration of manalagi apple's peel extract is 25%. The conclusion of this research proves that manalagi apple's peel extract has antibacterial activity against S.mutans growth.   Keywords: Antibacterial activity, manalagi apple's peels, Streptococcus mutans, well difussion method.